Letter (copy) : Spain - political assassinations - Tewson, Vincent
013-0053-001 International. HVT/AC/DT/321. 20th December, 1940. Mr. C. N. Gallie, Railway Clerks' Association, Midland Bank Chambers, Howardsgate, Welwyn Garden City. Dear Mr. Gallie, SPAIN - POLITICAL ASSASSINATIONS. I have your letter of the 18th of December in which you forward copy of a resolution from your Glasgow Central branch. In view of the statements made by the Chairman and myself at the last meeting of the General Council in regard to the steps which had been taken in respect of Largo Caballero and the inadvisability of our becoming too openly associated with requests for release, perhaps you will agree that we take note of the resolution only. Yours sincerely, Assistant Secretary. 292/946/13/53